基于遗传算法的贴标机凸轮机构运动规律研究 - 李靖; 何朝明; 庞胜军; 李欢 (Jixie chuandong)
The flexible impact of the conventional cam contour of the labeling machinery is analyzed,a new cam mechanism design method is proposed.Firstly,the movement condition and trajectory equation of the traditional cam mechanism are introduced,as well as the existence problems is pointed out.Secondly,under the given restrains,in order to realize multi-objective requirements of the follower segment angular acceleration of the acceleration curve is increasingly small as much as possible,the linear weighting method of multi-objective planning is used in the optimized analysis,the follower motion equation is redesigned by using the genetic algorithm.Once more,through solving the follower trajectory,then the cam contour is obtained by processing the trajectory.Finally,through after optimized cam profile,the cam mechanism is processed and the test running is carried out.The experimental results show that the cam mechanism of new design reduced the follower flexible impact,and it has a certain practical significance.